Adaptive emergency evacuation centre management for dynamic relocation of flood victims using firefly algorithm - Che Pa, Noraziah; Hashim, Nor Laily; Yusof, Yuhanis; Hussain, Azham (Universiti Teknikal Malaysia Melaka, 2016)
Situations during bad flood demands a systematic management of evacuation centres. Flood evacuation centres which are gazeted as temporary locations to evacuate flood victims have chances from being drowned by flood. Problem occurs to relocate flood victims when the evacuations centres are flooded. Currently, there is no study done on proposing a decision support aid to reallocate victims and resources of the evacuation centre when the situation getting worsens. Therefore, this article proposes a decision aid model to be utilized in realizing an adaptive emergency evacuation centre management system. This study undergoes two main phases; development of algorithm and models, and development of a web-based and mobile app. The proposed model operates using Firefly multi-objective optimization algorithm that creates an optimal schedule for the relocation of victims and resources for an evacuation centre. The proposed decision aid model and the adaptive system can be applied in supporting the National Security Council’s respond mechanisms for handling disaster management level II (State level) especially in providing better management of the flood evacuating centres.